Exploring RNA modifications in infectious non-coding circular RNAs - Pavel Vopalensky; Anton Škríba; Michela Chiumenti; Lucia Ďuričeková; Anna Šimonová; Ondřej Lukšan; Francesco Di Serio; Beatriz Navarro; Hana Cahova (RNA Biology)
Viroids, small circular non-coding RNAs, act as infectious pathogens in higher plants, demonstrating high stability despite consisting solely of naked RNA. Their dependence of replication on host machinery poses the question of whether RNA modifications play a role in viroid biology. Here, we explore RNA modifications in the avocado sunblotch viroid (ASBVd) and the citrus exocortis viroid (CEVd), representative members of viroids replicating in chloroplasts and the nucleus, respectively, using LC – MS and Oxford Nanopore Technology (ONT) direct RNA sequencing. Although no modification was detected in ASBVd, CEVd contained approximately one m6A per RNA molecule. ONT sequencing predicted three m6A positions. Employing orthogonal SELECT method, we confirmed m6A in two positions A353 and A360, which are highly conserved among CEVd variants. These positions are located in the left terminal region of the CEVd rod-like structure where likely RNA Pol II and and TFIIIA-7ZF bind, thus suggesting potential biological role of methylation in viroid replication.